2009
DOI: 10.4489/myco.2009.37.1.037
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Oyster Mushrooms on Lipid Profile, Liver and Kidney Function in Hypercholesterolemic Rats

Abstract: Comparative effects of oyster mushrooms on plasma and fecal lipid profiles and on liver and kidney function were evaluated in hyper and normocholesterolemic rats. Feeding of hypercholesterolemic rats a 5% powder of oyster mushrooms (Pleurotus ostreatus, P. sajor-caju and P. florida) reduced the plasma total cholesterol level by 37%, 21% and 16%, respectively and reduced the triglyceride level by 45%, 24% and 14%, respectively. LDL/HDL ratio decreased by 64%, 45% and 41% for P. sajor-caju, P. ostreatus and P. f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 26 publications
1
50
0
1
Order By: Relevance
“…Again serum bilirubin, creatinine and blood urea nitrogen (BUN) levels weredecreased in both hypercholesterolemic and mushroom fed hypercholesterolemic rats, but those were nonsignificant 13 .…”
Section: Introductionmentioning
confidence: 98%
“…Again serum bilirubin, creatinine and blood urea nitrogen (BUN) levels weredecreased in both hypercholesterolemic and mushroom fed hypercholesterolemic rats, but those were nonsignificant 13 .…”
Section: Introductionmentioning
confidence: 98%
“…Mushrooms are increasingly being recognized as important food products for their significant role in human health, nutrition and disease. Several species of mushrooms are of great importance because of their medicinal properties, for example, they are active against hypercholesterolemic conditions, hypertension, diabetes, cancer and other infections (Alam et al, 2007). Several studies have shown that P. pulmonarius and its extracts have many possible medicinal applications for a wide range of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Their ability to regulate the immune system, reduce lipid concentrations in the blood, and prevent high arterial pressure and sclerosis suggest that they have nutraceutical properties. These nutraceutical benefits are attributable to active biological compounds that frequently act as antioxidants (Alam et al 2009(Alam et al , 2011.…”
Section: Introductionmentioning
confidence: 99%